1989
DOI: 10.1111/j.1464-5491.1989.tb01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Awareness of Hypoglycaemia: Does it Change on Transfer from Animal to Human Insulin?

Abstract: A retrospective survey of symptomatic awareness of hypoglycaemia was performed in 189 randomly selected patients with insulin-treated diabetes who had been transferred from highly purified animal insulins to human insulin in the preceding 24 months. Of the 189 patients 44 (23%) complained of chronic hypoglycaemic unawareness, unrelated to ambient blood glucose control, before change of insulin species. Only 12 of the remaining 145 patients reported a reduction in awareness of hypoglycaemia following transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
(2 reference statements)
2
15
0
Order By: Relevance
“…These numbers correspond closely to those found by Hepburn et al (9) on the incidence of total (6%) or partial (17%) hypoglycemia unawareness when they investigated a group of insulintreated patients of similar age and duration of diabetes and used comparable clinical criteria for defining unawareness of hypoglycemia.…”
Section: Hypoglycemic Symptoms and Insulin Speciessupporting
confidence: 81%
See 2 more Smart Citations
“…These numbers correspond closely to those found by Hepburn et al (9) on the incidence of total (6%) or partial (17%) hypoglycemia unawareness when they investigated a group of insulintreated patients of similar age and duration of diabetes and used comparable clinical criteria for defining unawareness of hypoglycemia.…”
Section: Hypoglycemic Symptoms and Insulin Speciessupporting
confidence: 81%
“…However, such classifications of various warning symptoms are controversial. Thus, the symptoms hunger, unrest, anxiety, and visual disturbances have been classified either as autonomic or as neuroglycopenic symptoms (6,9,10). It has been calculated that by reallocating the symptoms unrest and anxiety in the study of Berger et al (6), the significance of the suggested difference between the two insulin species would have disappeared (11).…”
Section: Hypoglycemic Symptoms and Insulin Speciesmentioning
confidence: 97%
See 1 more Smart Citation
“…In the same journal, however, the authors also reported a study in which loss of concentration moved from fourth to first place in order of symptom importance to the patient during hypoglycemia (76). Nevertheless, hypoglycemic unawareness could not be correlated with use of human insulin in studies in Edinburgh (77), Germany (78), Denmark (79), Pittsburgh (80), or the U.S. in general (81). These studies were retrospective, but a recent prospective clinical study in Australia also has been negative (82).…”
Section: Human Insulin Counterregulation and Cognitive Function Inmentioning
confidence: 90%
“…The first seven symptoms were, however, the same on either insulin, and there was no increase in the frequency of severe hypoglycemia. In a study from Scotland, the 6% of patients who retrospectively described loss of hypoglycemic awareness on conversion to human insulin (27) were not many more than might have been expected to be losing awareness as a result of increasing disease duration (28). Negative studies of the frequency of severe hypoglycemia on the different insulins (24,29,30) have been criticized for being retrospective.…”
mentioning
confidence: 99%